Sastra Arab pada Masa Abbasiyah: Transformasi, Ekspansi, dan Tokoh-Tokoh Berpengaruh - Mega Rahmayani. AS; Muhsin; Haniah (El-Tarbawi : Jurnal Pendidikan Islam dan Humaniora, 2026)
The Abbasid Dynasty period (750–1258 CE) represents the most transformative era in the history of Arabic literature. This article aims to analyze the interrelationship between literary transformation, the expansion of genres and themes, and the contributions of prominent literary figures of that era as an interconnected and mutually influential whole. Employing a library research approach, this study examines various relevant literary sources to systematically identify the factors that shaped the development of Arabic literature. The findings reveal that the literary transformation of the Abbasid era was driven by three primary factors: the caliphs' policy of establishing Arabic as the official state language, the process of cultural assimilation with Persian, Turkish, and Indian civilizations, and the emergence of the badī' style as a new aesthetic innovation. Literary expansion occurred both qualitatively and quantitatively through the broadening of poetic themes from tribal characteristics toward philosophy and spirituality, as well as the emergence of new prose genres such as adab and maqāmāt, enriched through the translation movement at Bayt al-Hikmah. An examination of four influential figures Bashar ibn Burd, Abu Nawas, Abu al-Atahiyah, and Al-Mutanabbi reveals a diversity of literary expression that reflects the intellectual and social complexity of their time. This article concludes that the advancement of Abbasid Arabic literature was the result of a dialectical interaction among political policy, cultural openness, the patronage system, and the literary figures' courage to innovate, thereby establishing this period as the highest peak of literary achievement in the history of Arab civilization.